Analysis of Factors Influencing Households' Preference Level for Solar Energy in Urban Areas of Southwest Nigeria - Thompson, Olaniran Anthony; Ajiboye, Babatunde Oluseyi; Oluwamide, Akin Daniel; Oyenike, Olumide Ojo (International Journal of Energy Economics and Policy, 2021)
If Sustainable Development Goals (SDGs) seven of affordable and clean energy will be achieved, access to clean energy such as solar energy needs dedicated attention. The study assessed respondents' perception of solar energy and identified factors influencing their preference level in urban areas of Southwest Nigeria. Data were obtained from four hundred and eighty (480) solar energy users and four hundred and eighty (480) non- solar energy users leading to total of nine hundred and sixty (960) respondents' through a multi-stage sampling technique. Descriptive statistics, 5-likert scale type and tobit regression model were used to analyze the data collected. The respondents agreed that solar energy is the most appropriate source of energy compared to fossil fuel with mean score of 3.83. Price stability (0.83) attribute of solar energy is one of the reasons that makes it preferred by the respondent. A unit increase in household income will lead to 0.0879592 preference for solar energy in the study area. The study recommends that government at all levels should sensitize the households on the usage of solar energy in Nigeria to achieve the goal seven of SDGs. Keywords: Clean Energy, Solar Energy, Perception, Tobit Regression Model, Nigeria JEL Classifications: Q1, Q2, Q3 P28 DOI: https://doi.org/10.32479/ijeep.10001